Career management training in the university environment - Torres-Coronas, Teresa; Vidal-Blasco, María Arántzazu; Simón-Olmos, María José (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this paper we evaluate and confirm the effectiveness of including curriculum training on career management as a component of university studies. The behaviour of the students in this study was modified by the uncertainty created by the crisis in the labour market due to the pandemic. Our results confirm that universities need to develop the generic and academic skills demanded by the labour market in order to provide their students with comprehensive training while also taking joint responsibility for developing their students’ career management skills.